A picture of medically assisted reproduction activities during the COVID-19 pandemic in Europe. Issue 3 (17th August 2020) - ,; Vermeulen, Nathalie; Ata, Baris; Gianaroli, Luca; Lundin, Kersti; Mocanu, Edgar; Rautakallio-Hokkanen, Satu; Tapanainen, Juha S; Veiga, Anna
Abstract: STUDY QUESTION: How did coronavirus disease 2019 (COVID-19) impact on medically assisted reproduction (MAR) services in Europe during the COVID-19 pandemic (March to May 2020)? SUMMARY ANSWER: MAR services, and hence treatments for infertile couples, were stopped in most European countries for a mean of 7 weeks. WHAT IS KNOWN ALREADY: With the outbreak of COVID-19 in Europe, non-urgent medical care was reduced by local authorities to preserve health resources and maintain social distancing. Furthermore, ESHRE and other societies recommended to postpone ART pregnancies as of 14 March 2020. STUDY DESIGN, SIZE, DURATION: A structured questionnaire was distributed in April among the ESHRE Committee of National Representatives, followed by further information collection through email. PARTICIPANTS/MATERIALS, SETTING, METHODS: The information was collected through the questionnaire and afterwards summarised and aligned with data from the European Centre for Disease Control on the number of COVID-19 cases per country. MAIN RESULTS AND THE ROLE OF CHANCE: By aligning the data for each country with respective epidemiological data, we show a large variation in the time and the phase in the epidemic in the curve when MAR/ART treatments were suspended and restarted. Similarly, the duration of interruption varied. Fertility preservation treatments and patient supportive care for patients remained available during the pandemic. LARGE SCALE DATA: N/A LIMITATIONS, REASONS FOR CAUTION: Data collection was prone to misinterpretation of the questions and replies, and required further follow-up to check the accuracy. Some representatives reported that they, themselves, were not always aware of the situation throughout the country or reported difficulties with providing single generalised replies, for instance when there were regional differences within their country. WIDER IMPLICATIONS OF THE FINDINGS: The current article provides a basis for further research of the different strategies developed in response to the COVID-19 crisis. Such conclusions will be invaluable for health authorities and healthcare professionals with respect to future similar situations. STUDY FUNDING/COMPETING INTEREST(S): There was no funding for the study, apart from technical support from ESHRE. The authors had no COI to disclose.